ROOF WINDOW AND ROOF WINDOW ASSEMBLY METHOD IN A ROOF STRUCTURE - Ryszard, Florek (2025)
The subject-matter of the invention comprises a roof window and an assembly method for that window, constructed out of a jamb and a sash with a glass unit, and the roof window sash is seated in the jamb circumference using a pair of hinges, and the jamb is constructed out of four stiles attached to each other to form a rectangular frame, that is upper stile (11), lower stile (13) and two side stiles (12), wherein upper stile (11) in its assembled state in a roof is higher than all the other stiles in the roof, and jamb stiles feature window assembly in roof depth markers (4), characterized in that, in an assembled state in a roof, roof window slope angle α is within the 1-30° range and angle α is different than roof pitch angle β.